Penerapan Manajemen Perpustakaan dalam Upaya Meningkatkan Minat Baca Siswa SMP Bakti Ibu Lubuklinggau - Amora, Amora; Agussalim, Agussalim; Dwi Noviana Komsi; Supriadi, Supriadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the implementation of library management in an effort to increase student reading interest at Bakti Ibu Junior High School, Lubuklinggau. This study used a descriptive qualitative approach with a case study method, involving informants consisting of the head librarian, an Indonesian language teacher as literacy instructor, and students. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the interactive model of Miles et al. (2020) through the stages of data reduction, presentation, and verification, with validity maintained through triangulation of sources, time, and techniques. The results show that the implementation of library management functions at Bakti Ibu Junior High School, Lubuklinggau, includes four main stages: planning, organizing, implementing, and evaluating. The school has implemented various literacy programs such as 15-minute reading sessions, Book Week, Literacy Day, and the Schoology E-Learning Utilization Workshop. Collection management is carried out through a digital system supported by adequate infrastructure, although there are still obstacles such as limited budget, operating hours, and the absence of a professional librarian. The role of teachers and student participation in literacy activities also strengthen the effectiveness of library management. The findings indicate an increase in students' interest in reading, as evidenced by the increased frequency of library visits, participation in literacy activities, and intrinsic motivation to read. This study concludes that the implementation of systematic and participatory library management contributes significantly to increasing students' interest in reading. Effective library management encompasses not only the technical aspects of collection management but also strengthening literacy programs, integrating digital technology, and creating comfortable and inspiring reading spaces. Keywords: Library Management, Reading Interest, School Literacy, Educational Management